Welcome to Westonci.ca, where you can find answers to all your questions from a community of experienced professionals. Connect with a community of experts ready to help you find solutions to your questions quickly and accurately. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
To solve the equation [tex]\( z(2z + 1)(z + 3) = 0 \)[/tex], we need to find the values of [tex]\( z \)[/tex] that satisfy this equation. We can achieve this by factoring and using the zero-product property, which states that if the product of multiple factors equals zero, at least one of the factors must be zero.
Here’s the step-by-step solution:
1. Identify the factors:
The given equation is already factored to some extent:
[tex]\[ z(2z + 1)(z + 3) = 0 \][/tex]
2. Apply the zero-product property:
According to the zero-product property, for the product of these factors to be zero, at least one of the factors must be zero. Thus, we set each factor equal to zero separately:
[tex]\[ z = 0 \][/tex]
[tex]\[ 2z + 1 = 0 \][/tex]
[tex]\[ z + 3 = 0 \][/tex]
3. Solve each equation individually:
- For [tex]\( z = 0 \)[/tex]:
This is already solved. So, one solution is:
[tex]\[ z = 0 \][/tex]
- For [tex]\( 2z + 1 = 0 \)[/tex]:
Subtract 1 from both sides of the equation:
[tex]\[ 2z = -1 \][/tex]
Divide both sides by 2:
[tex]\[ z = -\frac{1}{2} \][/tex]
- For [tex]\( z + 3 = 0 \)[/tex]:
Subtract 3 from both sides:
[tex]\[ z = -3 \][/tex]
4. Combine the solutions:
The solutions to the equation [tex]\( z(2z + 1)(z + 3) = 0 \)[/tex] are:
[tex]\[ z = -3, \quad z = -\frac{1}{2}, \quad z = 0 \][/tex]
Thus, the complete set of solutions to the equation [tex]\( z(2z + 1)(z + 3) = 0 \)[/tex] is:
[tex]\[ z = -3, -\frac{1}{2}, 0 \][/tex]
Here’s the step-by-step solution:
1. Identify the factors:
The given equation is already factored to some extent:
[tex]\[ z(2z + 1)(z + 3) = 0 \][/tex]
2. Apply the zero-product property:
According to the zero-product property, for the product of these factors to be zero, at least one of the factors must be zero. Thus, we set each factor equal to zero separately:
[tex]\[ z = 0 \][/tex]
[tex]\[ 2z + 1 = 0 \][/tex]
[tex]\[ z + 3 = 0 \][/tex]
3. Solve each equation individually:
- For [tex]\( z = 0 \)[/tex]:
This is already solved. So, one solution is:
[tex]\[ z = 0 \][/tex]
- For [tex]\( 2z + 1 = 0 \)[/tex]:
Subtract 1 from both sides of the equation:
[tex]\[ 2z = -1 \][/tex]
Divide both sides by 2:
[tex]\[ z = -\frac{1}{2} \][/tex]
- For [tex]\( z + 3 = 0 \)[/tex]:
Subtract 3 from both sides:
[tex]\[ z = -3 \][/tex]
4. Combine the solutions:
The solutions to the equation [tex]\( z(2z + 1)(z + 3) = 0 \)[/tex] are:
[tex]\[ z = -3, \quad z = -\frac{1}{2}, \quad z = 0 \][/tex]
Thus, the complete set of solutions to the equation [tex]\( z(2z + 1)(z + 3) = 0 \)[/tex] is:
[tex]\[ z = -3, -\frac{1}{2}, 0 \][/tex]
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.